Evaluation of tribological properties of thermally sprayed tungsten carbide coating on AISI1045. (2023) - Muthukumar, S.; Ganesh, B.; Dilip Raja, N.; Selvam, M.
Abstract: The plasma based thermal coatings have been used for over five decades. The provision of plasma spray coatings on the low strength materials such as low carbon steels find prominent position in cost savings and replacement cycles of sliding components. Particularly the AISI 1045 based components find important role in automotives and marine structures. A clear understanding of the impact of thermal conditions on enhancement of surface characteristics for low carbon alloys during plasma spray coating is needed for deciding the lifecycle of products involving high temperature sliding conditions. Plasma Spray Coating was employed on AISI1045 plates and the improvement of strength, hardness and wear resistance along with the material composition was studied. Plasma Spray Coating is improved the wear resistance of AISI1045 sheets by 30 percent. The problems faced by the practicing professional such as frequent replacement of siding components and shorter life expectancy are reduced much by employing the thermal spray coating.